Screening for depression in cancer patients using the PHQ-9: the accuracy of somatic compared to non-somatic items - Grapp, Miriam; Terhoeven, Valentin; Nikendei, Christoph; Friederich, Hans-Christoph; Maatouk, Imad (Journal of affective disorders, 2019)
The PHQ-9 is a standard screening tool for depressive disorders in cancer patients. As for the frequently reported symptom overlap with somatic disease, it has been debated whether somatic items are suitable for identifying depressive disorders in cancer patients. Thus, this study examines the diagnostic accuracy of somatic versus cognitive-emotional PHQ-9 items. Methods: The routine data of 4,705 patients, screened at the National Center for Tumor Diseases in Heidelberg between 2011 and 2016, was analyzed. For the single PHQ-9 items, receiver operating characteristics (ROC), sensitivity, specificity, positive, and negative predictive values (PPV and NPV), the Youden Index (YI), and the Clinical Utility Index (UI+/UI-) were applied for the diagnoses of major depressive disorder (MDD) and any depressive disorder (ADD). Results: The non-somatic items played a pivotal role in the diagnosis of MDD, whereas the diagnostic accuracy of the somatic items increased in the diagnosis of ADD. For both MDD and ADD, the best performance was achieved by the non-somatic items “little interest” and “feeling down.” Limitations: In this study, only one self-reported instrument was used (i.e., the PHQ-9). In other words, the diagnoses were not validated by clinical interviews or other self-reported instruments. Conclusion: The somatic PHQ-9 items showed less discriminatory value than the non-somatic items. However, they may be useful as screening mechanisms for identifying at-risk cancer patients with mild/moderate depression. Disregarding the somatic items would lead to an underestimation of depressive syndromes and inadequate treatment of somatic symptoms.
Gesehen am 05.08.2019